Correlation between periodontal status and Parkinson's disease; a literature review - Dragoș Nicolae Ciongaru; Anca-Silvia Dumitriu; Bogdan Alexandru Dimitriu; Stana Păunică; Marina Cristina Giurgiu; Brânduşa Florina Mocanu; George Alexandru Popescu; Silviu Mirel Piţuru (Journal of Mind and Medical Sciences, 2024)
This systematic review aims to explore the relationship between chronic inflammation of periodontal disease and neurodegenerative disorders (especially Parkinson's disease), focusing primarily on pathophysiological, clinical and immunological aspects. An exhaustive search on this topic was performed in several databases (including PubMed, Scopus and Web of Science) selecting articles published between 2006 and 2023. After reviewing the titles, abstracts and protocols of each study, 13 articles were extracted for detailed assessment. The main indicators in the study included clinical signs of gingival inflammation, bleeding on probing (BoP), bone loss (BL), periodontal probing depth (PPD), and clinical attachment loss (CAL). Additionally, levels of inflammatory markers such as epidermal growth factor (EGF), interleukin-8 (IL-8), interleukin-17 (IL-17), interferon γ-induced protein 10 (IP-10), and monocyte chemoattractant protein-1 (MCP-1) were monitored. The investigation also explored the presence of one of the main periodontal pathogens (Porphyromonas gingivalis) in the microbiota of Parkinson's disease patients. In conclusion, the data presented further support the intricated relationship between periodontal health and neurodegenerative processes, including aspects related to changes in clinical periodontal indices, immunological indices, as well as oral hygiene and patient medication.